Always a guest : speaking of faith far from home - Taylor, Barbara Brown (Westminster John Knox Press, 2020)
"In this new collection of stories and sermons of faith, grace, and hope, Taylor finds that when you are the invited guest speaking of faith to people you don't know, you must seek common ground: exploring the central human experience"--